La naturaleza jurídica del trabajo penitenciario en Costa Rica - Rojas Rodríguez, Tatiana (2016)
What is the purpose of inmates’ prison labor? Its nature is rooted in Article 55 of the Criminal Code and in Law N° 4762, which provides that one of the functions of the Social Rehabilitation Directorate is the custody and treatment of any individuals who have been accused and sentenced.This law also allows convicts to reduce their sentence time through working at private entities or state institutions. This and other related laws provide the legal grounds of the manufacturing activities carried out by jail inmates, the main objective of which is to reduce their liberty-deprivation sentence, and also, to provide jail inmates with re-socialization opportunities.This is why, due to a lack of essential elements, in this type of relationship, the work done by inmates does not create any labor rights, as it was set forth by the Legislature: This is not an employment relationship.